Fuzzy neural hybrid position/force control for robot manipulators - Kiguchi, Kazuo; Fukuda, Toshio (Zielona Góra: Uniwersytet Zielonogórski)
Hybrid position/force control is one of the most important and fundamental control methods of robot manipulators. However, there are some problems in providing a hybrid position/force controller for practical use since conventional controllers are not able to adapt to an unknown environment.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka